ANALISIS KEPUASAN SISWA TERKAIT FLIPPED CLASSROOM SECARA BERGILIR DI SMP TAMAN DEWASA KOTA PROBOLINGGO - Puspitarini, Renny Candradewi; Lailatul Fitria, Nurul Jannah; Arianto, Aprillio Egy (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The pandemic period impacts every sector, including the education sector, which applies online learning. Right in 2021, the government will implement innovations in the teaching and learning system. Renewal of learning with Flipped Classroom Techniques at Face-to-Face Meetings in Turns. Of course, this renewal makes optimal use of the use of technology. The school that applies this technique is the Taman Dewasa Junior High School in Probolinggo City. This learning program is fairly new to be implemented in schools and is only known by students. So that its implementation needs to be monitored and assessed to improve the quality of services in the field of education, especially the Flipped Classroom program. The researcher conducted SKM research within the scope of the Taman Dewasa Junior High School in Probolinggo City. The method used is descriptive quantitative. Orientation of the instrument with observations and interviews in the form of a questionnaire via google form which was distributed to students of SMP Taman Dewasa Probolinggo City. There are 43 questions that describe 9 elements of public service. So that it can be seen the assessment of the SKM by students on the implementation of education services at the Taman Dewasa Junior High School in Probolinggo City. The results of the assessment indicate student satisfaction with the status of "agree" to good grades at school. In general, the level of student satisfaction related to learning with the flipped classroom technique at face-to-face meetings in rotation at the Taman Dewasa Junior High School in Probolinggo City is 75.55175. The quality of service is good by showing the SKM status in the "Agree" statement.